Metal contaminant risk at active floating photovoltaic sites and future research roadmap - Moreen Akomea-Ampeh; Eliot A. Atekwana; Elliott P. Steele; Alex E. Cagle; Alona Armstrong; Stephen J. Thackeray; Steven Sadro; Olusola O. Ololade; Olatubosun A. Fasipe; Rebecca R. Hernandez (Journal of Environmental Management, 2025)

A baseline assessment of contamination in the Sacramento deep water ship channel - Cristina G.B. La; Kara E. Huff Hartz; Mia Arkles; Melissa E. Grim; Shawn Acuña; Steven Sadro; Michael J. Lydy (Environmental Pollution, 2024)

Wildfire smoke impacts lake ecosystems - Mary Jade Farruggia; Janice Brahney; Andrew J. Tanentzap; Jennifer A. Brentrup; Ludmila S. Brighenti; Sudeep Chandra; Alicia Cortés; Rocio L. Fernandez; Janet M. Fischer; Alexander L. Forrest; Yufang Jin; Kenneth Larrieu; et al. (Global Change Biology, 2024)
Wildfire activity is increasing globally. The resulting smoke plumes can travel hundreds to thousands of kilometers, reflecting or scattering sunlight and depositing particles within ecosystems. Several key physical, chemical, and biological processes in lakes are controlled by factors affected by smoke. The spatial and temporal scales of lake exposure to smoke are extensive and under‐recognized. We introduce the concept of the lake smoke‐day, or the number of days any given lake is exposed to smoke in any given fire season, and quantify the total lake smoke‐day exposure in North America from 2019 to 2021. Because smoke can be transported at continental to intercontinental scales, even regions that may not typically experience direct burning of landscapes by wildfire are at risk of smoke exposure. We found that 99.3% of North America was covered by smoke, affecting a total of 1,333,687 lakes ≥10 ha. An incredible 98.9% of lakes experienced at least 10 smoke‐days a year, with 89.6% of lakes receiving over 30 lake smoke‐days, and lakes in some regions experiencing up to 4 months of cumulative smoke‐days. Herein we review the mechanisms through which smoke and ash can affect lakes by altering the amount and spectral composition of incoming solar radiation and depositing carbon, nutrients, or toxic compounds that could alter chemical conditions and impact biota. We develop a conceptual framework that synthesizes known and theoretical impacts of smoke on lakes to guide future research. Finally, we identify emerging research priorities that can help us better understand how lakes will be affected by smoke as wildfire activity increases due to climate change and other anthropogenic activities.

Internal phosphorus loading alters nutrient limitation and contributes to cyanobacterial blooms in a polymictic lake - Micah M. Swann; Alicia Cortes; Alexander L. Forrest; Nick Framsted; Steven Sadro; S. Geoffrey Schladow; Angela De Palma-Dow (Aquatic Sciences, 2024)
Clear Lake, a medium-sized hypereutrophic, polymictic lake in northern California, has had recurring harmful cyanobacteria blooms (HCBs) for over a century despite reductions in external phosphorus (P) loadings. Internal P loading can alter nutrient availability and limitation supporting HCBs but is rarely quantified or compared with external loads. We have quantified external P loads from 2019 to 2021 for the three main tributaries (accounting for 46% of the flow) and internal loadings using two methods: a P mass balance and modeled release rates of soluble reactive phosphorus from oxic and anoxic sediments. In addition, we combined high-frequency in situ measurements of water temperature and dissolved oxygen, discrete grab sampling for nutrient chemistry, and remote sensing to explore the potential drivers of the observed variability and provide a comprehensive view of the spatiotemporal dynamics of HCBs. By understanding the relative contribution of external and internal nutrient loadings and the relationship between environmental parameters and HCBs, interannual bloom variability can be better predicted. Comparative estimates of external and internal phosphorus loading indicate that internal sources accounted for 70–95% of the total P input into the system during the study period. Contrary to other lakes, the intensity of the summer bloom season was correlated to the timing and duration of anoxia rather than the magnitude of spring runoff. Internally released P shifted the system from phosphorus to nitrogen limitation during the summer, potentially favoring the proliferation of nitrogen-fixing cyanobacteria.

Oxygen depletion and sediment respiration in ice‐covered arctic lakes - Robert Schwefel; Sally MacIntyre; Alicia Cortés; Steven Sadro (Limnology and Oceanography, 2023)
Processes regulating the rate of oxygen depletion determine whether hypoxia occurs and the extent to which greenhouse gases accumulate in seasonally ice‐covered lakes. Here, we investigate the oxygen budget of four arctic lakes using high‐frequency data during two winters in three shallow lakes (9–13 m maximal depth) and four winters in 24 m deep main basin of Toolik Lake. Incubation experiments measured sediment metabolism. Volume‐averaged oxygen depletion measured in situ was independent of water temperature and duration of the ice‐covered period. Average rates were between 0.2 and 0.39 g O 2 m −2 d −1 in the shallow lakes and between 0.03 and 0.14 g O 2 m −2 d −1 in Toolik Lake, with higher rates in smaller lakes with their larger sediment area to volume ratio. Rates decreased to ~ 20%–50% of initial values in late winter in the shallow lakes but less or not at all in Toolik. The lack of a decline in Toolik Lake points to continued oxygen transport to the sediment–water interface where oxygen consumption occurs. In all lakes, lower in situ oxygen depletion than in incubation measurements points toward increasing anoxia in the lower water column depressing loss rates. In Toolik, oxygen loss during early winter was less in years with minimal snow cover. Penetrative convection occurred, which could mix downwards oxygen produced by photosynthesis or excluded during ice formation. Estimates of these terms exceeded photosynthesis measured in sediment incubations. Modeling under ice‐oxygen dynamics requires consideration of optical properties and biological and transport processes that modify oxygen concentrations and distributions.

Whole-Ecosystem Experiment Illustrates Short Timescale Hydrodynamic, Light, and Nutrient Control of Primary Production in a Terminal Slough - Luke C. Loken; Steven Sadro; Leah E. K. Lenoch; Paul R. Stumpner; Randy A. Dahlgren; Jon R. Burau; Erwin E. Van Nieuwenhuyse (Estuaries and Coasts, 2022)
Estuaries are among the most productive of aquatic ecosystems. Yet the collective understanding of patterns and drivers of primary production in estuaries is incomplete, in part due to complex hydrodynamics and multiple controlling factors that vary at a range of temporal and spatial scales. A whole-ecosystem experiment was conducted in a deep, pelagically dominated terminal channel of the Sacramento-San Joaquin Delta (California, USA) that seasonally appears to become nitrogen limited, to test whether adding calcium nitrate would stimulate primary productivity or increase phytoplankton density. Production did not respond consistently to fertilization, in part because nitrate and phytoplankton were dispersed away from the manipulated area within 1–3 days. Temporal and spatial patterns of gross primary production were more strongly related to stratification and light availability (i.e., turbidity) than nitrogen, highlighting the role of hydrodynamics in regulating system production. Similarly, chlorophyll was positively related not only to stratification but also to nitrogen—with a positive interaction—suggesting stratification may trigger nutrient limitation. The average rate of primary production (4.3 g O 2 m −2 d −1 ), metabolic N demand (0.023 mg N L −1 d −1 ), and ambient dissolved inorganic nitrogen concentration (0.03 mg N L −1 ) indicate that nitrogen can become limiting in time and space, especially during episodic stratification events when phytoplankton are isolated within the photic zone, or farther upstream where water clarity increases, dispersive flux decreases, and stratification is stronger and more frequent. The role of hydrodynamics in organizing habitat connectivity and regulating physical and chemical processes at multiple temporal and spatial scales is critical for determining resource availability and evaluating biogeochemical processes in estuaries.

Earlier winter/spring runoff and snowmelt during warmer winters lead to lower summer chlorophyll‐ a in north temperate lakes - Allison R. Hrycik; Peter D. F. Isles; Rita Adrian; Matthew Albright; Linda C. Bacon; Stella A. Berger; Ruchi Bhattacharya; Hans‐Peter Grossart; Josef Hejzlar; Amy Lee Hetherington; Lesley B. Knoll; Alo Laas; et al. (Global Change Biology, 2021)
Winter conditions, such as ice cover and snow accumulation, are changing rapidly at northern latitudes and can have important implications for lake processes. For example, snowmelt in the watershed—a defining feature of lake hydrology because it delivers a large portion of annual nutrient inputs—is becoming earlier. Consequently, earlier and a shorter duration of snowmelt are expected to affect annual phytoplankton biomass. To test this hypothesis, we developed an index of runoff timing based on the date when 50% of cumulative runoff between January 1 and May 31 had occurred. The runoff index was computed using stream discharge for inflows, outflows, or for flows from nearby streams for 41 lakes in Europe and North America. The runoff index was then compared with summer chlorophyll‐ a (Chl‐ a ) concentration (a proxy for phytoplankton biomass) across 5–53 years for each lake. Earlier runoff generally corresponded to lower summer Chl‐ a . Furthermore, years with earlier runoff also had lower winter/spring runoff magnitude, more protracted runoff, and earlier ice‐out. We examined several lake characteristics that may regulate the strength of the relationship between runoff timing and summer Chl‐ a concentrations; however, our tested covariates had little effect on the relationship. Date of ice‐out was not clearly related to summer Chl‐ a concentrations. Our results indicate that ongoing changes in winter conditions may have important consequences for summer phytoplankton biomass and production.

The extent and variability of storm‐induced temperature changes in lakes measured with long‐term and high‐frequency data - Jonathan P. Doubek; Orlane Anneville; Gaël Dur; Aleksandra M. Lewandowska; Vijay P. Patil; James A. Rusak; Nico Salmaso; Christian Torsten Seltmann; Dietmar Straile; Pablo Urrutia‐Cordero; Patrick Venail; Rita Adrian; et al. (Limnology and Oceanography, 2021)
The intensity and frequency of storms are projected to increase in many regions of the world because of climate change. Storms can alter environmental conditions in many ecosystems. In lakes and reservoirs, storms can reduce epilimnetic temperatures from wind‐induced mixing with colder hypolimnetic waters, direct precipitation to the lake's surface, and watershed runoff. We analyzed 18 long‐term and high‐frequency lake datasets from 11 countries to assess the magnitude of wind‐ vs. rainstorm‐induced changes in epilimnetic temperature. We found small day‐to‐day epilimnetic temperature decreases in response to strong wind and heavy rain during stratified conditions. Day‐to‐day epilimnetic temperature decreased, on average, by 0.28°C during the strongest windstorms (storm mean daily wind speed among lakes: 6.7 ± 2.7 m s −1 , 1 SD) and by 0.15°C after the heaviest rainstorms (storm mean daily rainfall: 21.3 ± 9.0 mm). The largest decreases in epilimnetic temperature were observed ≥2 d after sustained strong wind or heavy rain (top 5 th percentile of wind and rain events for each lake) in shallow and medium‐depth lakes. The smallest decreases occurred in deep lakes. Epilimnetic temperature change from windstorms, but not rainstorms, was negatively correlated with maximum lake depth. However, even the largest storm‐induced mean epilimnetic temperature decreases were typically

Low Levels of Allochthony in Consumers Across Three High-Elevation Lake Types - Michael J. Vlah; Gordon W. Holtgrieve; Steven Sadro (Ecosystems, 2018)

Flowpath and retention of snowmelt in an ice‐covered arctic lake - Alicia Cortés; Sally MacIntyre; Steven Sadro (Limnology and Oceanography, 2017)
The extent to which snowmelt flowing into ice‐covered lakes spreads horizontally and mixes vertically influences retention of solutes derived from the landscape. To quantify these transport processes and retention, we combine time series temperature and specific conductance measurements in Toolik Lake (Alaska) and its major inflow, with measurements of discharge and meteorology, and profiles of specific conductance, temperature, fluorescence, chlorophyll a , and dissolved organic carbon (DOC) in spring of 3 yr. During early snowmelt, the concentration of DOC in the stream was 750 μM, twice that in the lake. During slow melt (discharge ( Q ) 3 s −1 ), the incoming solute‐rich intrusion spread lakewide below the ice. During melt with Q > 6 m 3 s −1 , the incoming water partially flushed the inlet basin and the more dilute water flowed over the original intrusion with a preferential flowpath to the outlet. Penetrative convection was restricted by the increased density gradients from the incoming plume and initially constrained to shallow mixing zones associated with the step changes in density. As ice thickness decreased to less than 1 m, heating caused density instabilities at the base of the intrusions that mixed solutes ∼ 10 m vertically, contributing to retention. Near‐surface layers enriched with DOC persisted for ∼ 10 d during a rapid melt and for over 3 weeks when the melt was slow. Retention, of order 10–20%, also depended on the rapidity of melt and magnitude of discharge.

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Ecosystem Consequences of Changing Inputs of Terrestrial Dissolved Organic Matter to Lakes: Current Knowledge and Future Challenges - Christopher T. Solomon; Stuart E. Jones; Brian C. Weidel; Ishi Buffam; Megan L. Fork; Jan Karlsson; Søren Larsen; Jay T. Lennon; Jordan S. Read; Steven Sadro; Jasmine E. Saros (Ecosystems, 2015)

Widespread variability in overnight patterns of ecosystem respiration linked to gradients in dissolved organic matter, residence time, and productivity in a global set of lakes - Steven Sadro; Gordon W. Holtgrieve; Christopher T. Solomon; Gregory R. Koch (Limnology and Oceanography, 2014)
We characterized patterns of nighttime ecosystem respiration (ER) in 23 globally‐distributed lakes using free‐water changes in dissolved oxygen (DO). We considered three alternative models of ER to describe overnight changes in DO: constant ER, linearly declining ER, or logistically declining ER. Variation in ER was widespread. Each model of respiration was found to best fit observed overnight DO dynamics with some degree of frequency in every lake. Constant ER occurred with an average frequency of 62% across lakes and was most commonly the best description of DO dynamics. It never occurred with a frequency

The Influence of Landscape Position and Catchment Characteristics on Aquatic Biogeochemistry in High-Elevation Lake-Chains - Steven Sadro; Craig E. Nelson; John M. Melack (Ecosystems, 2012)

Spatial and Temporal Variability in the Ecosystem Metabolism of a High-elevation Lake: Integrating Benthic and Pelagic Habitats - Steven Sadro; John M. Melack; Sally MacIntyre (Ecosystems, 2011)

Depth‐integrated estimates of ecosystem metabolism in a high‐elevation lake (Emerald Lake, Sierra Nevada, California) - Steven Sadro; John M. Melack; Sally MacIntyre (Limnology and Oceanography, 2011)
A series of vertical profiles of dissolved oxygen (DO) collected periodically over two consecutive ice‐free seasons in an oligotrophic high‐elevation lake (Emerald Lake, California) were used to investigate volumetric and areal rates of gross primary production (GPP), community respiration (CR), and net ecosystem production (NEP). Diel patterns in DO did not weaken with depth in this lake, where the entire 10‐m water column was within the euphotic zone and where a deep chlorophyll a (Chl a ) maximum was common during periods of thermal stratification. During stratification, both GPP and CR increased with depth, and heterotrophy (NEP a and particulate matter concentrations. With the onset of autumn mixing each year, vertical gradients in metabolism weakened or disappeared and the entire water column was autotrophic. Net autotrophy over the growing season was confirmed using three methods of estimating whole‐lake metabolism. During periods of stratification, flux across the thermocline, where eddy diffusivities were near molecular, was small (4% of total epilimnetic fluxes), while within the hypolimnion, where stratification was weaker and eddy diffusivities larger, fluxes between strata were more substantial (12% of total fluxes). For this lake and other small lakes with low wind speeds and Lake numbers near 10, mixing due to turbulence should be included in computations of metabolism within the hypolimnion. However, single‐station measurements from within the epilimnion provide a reasonable estimate of seasonal metabolism, especially in the autumn when the lake is mixing on a diel basis.

Linking diel patterns in community respiration to bacterioplankton in an oligotrophic high‐elevation lake - Steven Sadro; Craig E. Nelson; John M. Melack (Limnology and Oceanography, 2011)
We examined the role of heterotrophic bacterioplankton in structuring diel patterns in community respiration (CR) in an oligotrophic alpine lake. We used continuous measurements of dissolved oxygen from both free‐water and in situ incubation chambers to characterize a consistent diel pattern in oxygen drawdown with two distinct phases. CR rates averaged 15.4 times higher during the late afternoon to early night phase, which lasted for up to 5 h past dusk before rapidly transitioning to the lower rate phase, which lasted through dawn. Bacterioplankton always accounted for the majority of CR (73% seasonally averaged). We examined patterns in dissolved organic carbon (DOC) and bacterial growth to determine the degree to which bacterioplankton were affecting diel variability in respiration rates. There was a diel pattern in DOC accumulation, with the magnitude of overnight drawdown of DOC (2.0 ± 0.8 μmol L −1 ) matching our oxygen‐based estimates of the amount of DOC required to sustain higher CR rates (2.4 ± 1.3 μmol L −1 ). Bacterioplankton communities cultured on dusk water had growth‐rate constants two times higher than those cultured on dawn water and removed the excess DOC in dusk water. Our results indicate that higher daytime CR of bacterioplankton is directly coupled to daily production of DOC at a timescale of hours, likely through phytoplankton exudation. Ignoring diel variability in CR may result in substantial underestimation of daily CR and gross primary production.

Contrasting the influences of stream inputs and landscape position on bacterioplankton community structure and dissolved organic matter composition in high‐elevation lake chains - Craig E. Nelson; Steven Sadro; John M. Melack (Limnology and Oceanography, 2009)
We examined bacterioplankton community composition (BCC; using polymerase chain reaction‐based phylogenetic fingerprinting) and the composition of dissolved organic matter (DOM; using scanning fluorometry) within lake chains in high‐elevation catchments of the Sierra Nevada, California. We compared temporal BCC dynamics in two connected cirque lakes and their inlets and found that lake : inlet community similarity of both lakes declined with increasing residence time because of seasonal snowpack melting. However, for over 3 yr the headwater lake remained distinct from its inlet even during peak snowmelt (residence time